Does Hsp60 Provide a Link between Mitochondrial Stress and Inflammation in Diabetes Mellitus? - Juwono, Joshua (J Diabetes Res, 2016)
The focus of this review is to summarise the known relationships between the expression of heat shock protein 60 (Hsp60) and its association with the pathogenesis of Type 1 and Type 2 diabetes mellitus. Hsp60 is a mitochondrial stress protein that is induced by mitochondrial impairment. It is known to be secreted from a number of cell types and circulating levels have been documented in both Types 1 and 2 diabetes mellitus patients. The biological significance of extracellular Hsp60, however, remains to be established. We will examine the links between Hsp60 and cellular anti- and proinflammatory processes and specifically address how Hsp60 appears to affect immune inflammation by at least two different mechanisms: as a ligand for innate immune receptors and as an antigen recognised by adaptive immune receptors. We will also look at the role of Hsp60 during immune cell activation in atherosclerosis, a significant risk factor during the pathogenesis of diabetes mellitus.